Enhancing the Growth of Water Spinach (Ipomoea reptans L.) through the Application of Chicken Bone Waste-Based Fertilizer in Ultisol Soil - Rahima Taher; Suwirmen; Zozy Aneloi Noli (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to evaluate the effects of the dosage and application frequency of chicken bone meal on the growth of water spinach (Ipomoea reptans L.). The experiment employed a factorial design within a completely randomized design (CRD) consisting of two factors, namely chicken bone meal dosage and application frequency. The observed parameters included plant height, number of leaves, and plant dry weight. The results showed that both the dosage and application frequency of chicken bone meal significantly affected the growth of water spinach. A dosage of 60 g produced the highest dry weight, reaching 20.76 g, compared with 6.10 g in the control treatment, while an application frequency of once per week resulted in better plant growth. The interaction effect indicated that the A3B1 combination produced the best growth performance, with dry weight reaching 24.97 g. Therefore, the application of chicken bone meal at an appropriate dosage and frequency can optimize the growth of water spinach.